(5*n)-16=-39

Simple and best practice solution for (5*n)-16=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5*n)-16=-39 equation:


Simplifying
(5n) + -16 = -39

Reorder the terms:
-16 + (5n) = -39

Solving
-16 + (5n) = -39

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + (5n) = -39 + 16

Combine like terms: -16 + 16 = 0
0 + (5n) = -39 + 16
(5n) = -39 + 16

Combine like terms: -39 + 16 = -23
(5n) = -23

Divide each side by '5'.
n = -4.6

Simplifying
n = -4.6

See similar equations:

| -15d=0 | | f(x)=(6-x)(x-2)(x+7) | | 8s=152 | | 1+3x=85 | | 23+(3*n)=95 | | 10-d=3-5d | | f(x)=x^3-14x^2+49x | | 9*r=135 | | b+250=500 | | 14*x=238 | | x^3+3x^2=x^2 | | 3y=3+75/19 | | 5x=(2x-2)(m+4) | | P(x)=x^4-9x+5x^2-7x+10 | | 3x^2+30x+70=0 | | -10+8y=13y+5 | | S=2-b | | S=b-2 | | c=5/9(15-32) | | 139.11=2.85h+73.56 | | 91=w/7 | | 19-2k=3k-1 | | 3(x-2)-2(x+4)=0 | | -4+2x=4x-6 | | -3=4(x+4)-5x | | 4x^2-24y+4x+49=0 | | 3hk+6hk+6hk=15hk | | 1/6(x)+x=24 | | 3x+23-x+23=-2 | | 3(x+5)-6=15 | | 3x-6=2*(x+5)-3 | | 2e+5=31 |

Equations solver categories